(untitled) (Global Journal of Medical Research, 2016)
Background Rheumatoid arthritis RA is a chronic inflammatory disorder of unknown etiology characterized by systemic symptoms that particularly involve the joints and may lead to deformities during the course of the disease It is the most common persistent inflammatory arthritis occurring throughout the world and in all ethnic groups Objectives To find out the association of metabolic syndrome in rheumatoid arthritis patients as compared to healthy individuals Methods This case control study was carried out with 50 patients of rheumatoid arthritis case and 50 apparently healthy individual controls in Biochemistry Department Dhaka Medical College Dhaka from July 2014 to June 2015 After overnight fast at least 8 hrs venous sample was taken from each subject